Tahapan Audit Koding Rekam Medis dengan Menggunakan Analisa Kualitatif pada Pasien Rawat Inap di RS Khusus Mata SMEC Tahun 2025 - Hutasoit, Theresia; Daeli, Cosmas Samuel; Sitorus, Mei Sryendang; Simanjuntak, Marta; Rotonga, Zulham Andi; Hasibuan, Ali Sabela; Liem, John Barker; Valentina, Valentina; Zulfahmi, Zulfahmi; Sitompul, Osayku Inesa (Universitas Pahlawan Tuanku Tambusai, 2026)
Medical records are crucial documents that document all healthcare services. Accurate coding forms the basis for claims billing, research, and clinical decision-making. However, incomplete and inaccurate recording often presents obstacles, necessitating a coding audit. This Community Service project aimed to identify the stages of a coding audit using qualitative analysis of inpatients. The audit was conducted on four cases. The analysis used six review components: consistency of diagnosis and treatment, clinical recording, treatment justification, informed consent, documentation practices, and potential for compensation. The results of the medical record coding audit indicated that most components were consistent and met standards, including diagnosis, treatment, clinical recording, and completion of informed consent. However, inconsistencies were still found in instructions for discontinuing or replacing medications. There were no incidents that could potentially result in compensation. However, improvements are still needed in the documentation of instructions for discontinuing or replacing medications. The results emphasize the importance of ongoing socialization and monitoring to optimize the quality of medical records.